EFFECT OF HYPNOBIRTHING ON THE PROGRESS OF THE LATENT PHASE OF LABOR IN PRIMIGRAVIDA - Wiwik Mudihayati; Syarif Thaufik Hidayat; Nur Khafidhoh; Ari Suwondo (Belitung Raya Foundation, Indonesia, 2018)
Background: The first stage of labor is a tiring moment for mothers, which may cause exhaustion, dehydration, risk of infection, uterine atony, and postpartum hemorrhage. Hypnobirthing is considered effective to speed up early labor process. Objective: This study aimed to examine the effect of hypnobirthing on the progress of the latent phase of labor. Methods: This study was a quasi-experiment with posttest only control group design. Thirty-two primigravida mothers in the latent phase of labor were selected using purposive sampling, with 16 assigned in the experiment group and the control group. The progress of labor was measured by four indicators recorded in partograph, namely frequency and duration of uterine contraction, cervical dilatation, and descent of the fetal head. Independent t-test was used for data analysis. Results: There was a significant difference in the frequency of uterine contraction (p=0.001), duration of contraction (p=0.001), cervical dilatation (p=0.007), and descent of the fetal head (p=0.001) between the experiment group and the control group. Conclusion: Hypnobirthing technique is significant in accelerating the progress of the latent phase of labor in primigravida mothers.